Who Stays On? The Link between Psychosocial Patterns and Changes in Exercise and Sport Behaviour When Adolescents Make Transitions in Education. Issue 2 (10th October 2019) - Schmid, Julia; Gut, Vanessa; Yanagida, Takuya; Conzelmann, Achim
Abstract : Background: The first aim of the present study was to identify psychosocial patterns among adolescents at lower secondary school. Employing the motivation and volition process model and a socioecological framework, self‐concordance, action planning, social support, and club‐related exercise and sport activities were included as indicators. The second aim was to examine how these patterns are associated with the maintenance of exercise and sport during students' transition to upper secondary education. The last aim was to investigate whether the associations were moderated by individuals' subjective evaluation of the transition. Methods: One‐year longitudinal data of 392 adolescents were analysed. All variables were measured via online self‐report. Results: Based on latent profile analysis, four patterns were found: "averages", "club enthusiasts", "club engaged planners", and "less motivated and social uncommits". Regression analyses showed that the club engaged planners were more likely to adopt and maintain exercise and sport than to drop out. Additionally, moderation analyses revealed that the averages were less likely to be maintainers/adopters when they evaluated the transition more negatively. Conclusion: People with relatively high action planning and a high number of club‐related activities were less vulnerable to decreasing their activity time during the transition to upper secondary education. Furthermore, transitional stress bore no negative association with students' exercise and sport behaviour.